AL-‘ĀLAM DALAM ALQURAN: (Analisis tentang Ayat-ayat Penciptaan) - Muhammad Syarif Hasyim (State Institute of Islamic Studies (IAIN) Palu, 2012)
Abstract: One of the objects of the philosophy studies is the nature. The thought of the nature runs continually to the things beyond the nature (metaphysics) and eventually comes to a conclusion that the existence of the nature must be in process. The philosophers argued that all things created must be in process, namely the process of emanation. The implication of this argument is that the nature is qadīm, because it was created by God since qidam and azālī. This argument was opposed by the theologists (mutakallimīn). They said that the nature was something new and its existence was from nothing. These two different theories are supported by the dalīls of the Qur’an. Their interpretations on the verses of the Qur’an gave the opportunity to result in different argument. The reason is that the use of the terms in the Qur’an, which refer to the meaning of creating, is various, moreover when referring to the proposition which rejects the existence of the synonims in the Qur’an. Therefore, eventhough the meaning of the term “khalaqa, bada‘a and fatara is “to create”, each this single word has its own substancial meaning.Kata Kunci: Alquran, filsafat, penciptaan alam, khalaqa, bada‘a, fatara